2015
DOI: 10.1093/jjco/hyv058
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Aurora kinase A (AURKA) expression among solid tumor patients: a systematic review and meta-analysis

Abstract: Objective: The prognostic significance of Aurora kinase A expression in cancer patients is currently under debate. Here, we conducted the first comprehensive meta-analysis of the prognostic relevance of Aurora kinase A associated with survival in solid tumors. Methods: Pubmed was searched for studies evaluating the Aurora kinase A expression and survival in solid tumors through 10 October 2014. The main outcome analyzed was overall survival and secondary outcomes were progression-free survival, disease-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…As such, caution should be exercised regarding the associations between gene regulation by miRNAs and patient prognosis. Nonetheless, we have recovered known associations in our survival analyses, some of which have been studied extensively in many tumours, like the roles on prognosis of genes AURKA 50515253 or BRCA1 5455. We also found novel stage-independent prognostic genes not described in the literature like CASC5 .…”
Section: Discussionmentioning
confidence: 61%
“…As such, caution should be exercised regarding the associations between gene regulation by miRNAs and patient prognosis. Nonetheless, we have recovered known associations in our survival analyses, some of which have been studied extensively in many tumours, like the roles on prognosis of genes AURKA 50515253 or BRCA1 5455. We also found novel stage-independent prognostic genes not described in the literature like CASC5 .…”
Section: Discussionmentioning
confidence: 61%
“…Of the 18 patients with CRPC, 14 (78%) were evaluable by either RECIST or PSA response criteria . The ORR was 43% (6 of 14) and included either PSA or RECIST.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of aurora A kinase (AAK) is carcinogenic and has been implicated in the development of breast, bladder, colon, ovarian, pancreatic, and stomach cancers . After cancer development, the levels of AAK may be prognostic of survival, with increased levels correlating with shorter survival …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to AURKA, these results are in alignment with the results of Zhang et al who demonstrated that AURKA expression was significantly associated with a shorter OS by systematic review and meta-analysis in various solid tumors. For BC exclusively, the AURKA expression levels were not significantly associated with poor prognosis but patients receiving the AURKA inhibitor alisertib in a phase II study, showed significant response [63]. …”
Section: Discussionmentioning
confidence: 99%